1996
DOI: 10.2307/524946
|View full text |Cite
|
Sign up to set email alerts
|

Eritrean and Ethiopian Urban Refugees in Khartoum: What the Eye Refuses to See

Abstract: A decade and a half ago Chambers (1979) referred to African rural refugees as “What the Eye Does not See.” This was, inter alia, due to the remoteness of their inhabited areas and the urban bias which then characterized the responses of the international assistance regime. If rural refugees were, in the 1970s, “what the eye did not see,” today refugees in many of the African urban centers are what the eye “refuses to see.” One of the most dramatic and far-reaching impacts of war, drought and economic hardship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 20 publications
(4 reference statements)
0
28
0
Order By: Relevance
“…Second, females are over-represented in forced migration flows from African countries affected by wars (Pedraza 1991). Although, it is difficult, if not impossible, to identify the contribution of female professionals to this process, the higher representation of females in many African forced-migrant populations is now well documented (Ager, Ager, and Long 1995, Kibreab 1996, Martin 2004). Lubkemann (2000), for instance, has described large female migration flows from Mozambique to Zimbabwe and South Africa during the Mozambican civil war.…”
Section: Conceptualizing Female Participation In Aimmentioning
confidence: 99%
“…Second, females are over-represented in forced migration flows from African countries affected by wars (Pedraza 1991). Although, it is difficult, if not impossible, to identify the contribution of female professionals to this process, the higher representation of females in many African forced-migrant populations is now well documented (Ager, Ager, and Long 1995, Kibreab 1996, Martin 2004). Lubkemann (2000), for instance, has described large female migration flows from Mozambique to Zimbabwe and South Africa during the Mozambican civil war.…”
Section: Conceptualizing Female Participation In Aimmentioning
confidence: 99%
“…Another study conducted among the refugees in Khartoum also showed that the male spouses of some of the FHHs were working either in the Gulf States or in one of the countries in Western Europe and/or North America, or in Australia or New Zealand (Kibreab, 1996b). Among a sample of 432 household heads, 50 per cent of the females were married and were living together with their husbands, 29 per cent were single, 2 per cent cohabiting without being married (semur ginbar), 8 5 per cent divorced and separated, 4 per cent widowed, and the spouses of another 10 per cent lived outside Sudan (Kibreab, 1996b).…”
Section: Household Composition Of the Returnees Prior To Repatriationmentioning
confidence: 94%
“…Among a sample of 432 household heads, 50 per cent of the females were married and were living together with their husbands, 29 per cent were single, 2 per cent cohabiting without being married (semur ginbar), 8 5 per cent divorced and separated, 4 per cent widowed, and the spouses of another 10 per cent lived outside Sudan (Kibreab, 1996b). The family structure of Eritrean refugees in Khartoum also exhibited some unusual forms in the sense that a large proportion (20 per cent) of the`households' comprised groups of bachelors who in order to make ends meet, shared incomes, expenditures and housing (Kibreab, 1996b). Though these households comprised adults of the same sex without any sexual relationship, the arrangements involved common residence and economic co-operation and therefore fit the standard definition of households.…”
Section: Household Composition Of the Returnees Prior To Repatriationmentioning
confidence: 99%
“…Aside from intracountry movement, Ethiopia has been ''one of the most important refugee-generating countries of the world for the past 20 years'' (Bariagaber, 1997, p. 30). A further large, but uncounted number of people crossed into Sudan as a result of resettlement and other government policies in the 1980s (Kibreab, 1996), but once again, the number of individuals involved remains unknown.…”
Section: Interpretation Of Mapped Changesmentioning
confidence: 99%